2019
DOI: 10.1021/acs.langmuir.9b00607
|View full text |Cite
|
Sign up to set email alerts
|

Facile Transfer of Reverse Micelles from the Organic to the Aqueous Phase for Mimicking Enzyme Catalysis and Imaging-Guided Cancer Therapy

Abstract: Reverse micelles (RMs) with confined water pools have been applied in many fields. However, the water insolubility of RMs seriously limits the scope of their application, especially those needed to operate in aqueous environments. Here, we report the first successful transfer of RMs from the organic phase to water phase without disturbing their confined water pools and hydrophobic alkyl region. This transfer was achieved by virtue of a mild host–guest interaction between the hydrophobic tails of interfacial cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
1
9
0
Order By: Relevance
“…The dynamic light scattering (DLS) measurement showed that, after transfer, the AICRM retains a particle size of ≈18 nm, comparable to that before transfer (≈15 nm, Figure 1b). [ 15a ] Representative transmission electron microscopy (TEM) showed that the nanoparticles were evenly dispersed, and diameters of 15–20 nm were consistent with DLS results (Figure 1c). The cross‐linked reverse micelles have good stability in blood environment and resist extreme dilution.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations
“…The dynamic light scattering (DLS) measurement showed that, after transfer, the AICRM retains a particle size of ≈18 nm, comparable to that before transfer (≈15 nm, Figure 1b). [ 15a ] Representative transmission electron microscopy (TEM) showed that the nanoparticles were evenly dispersed, and diameters of 15–20 nm were consistent with DLS results (Figure 1c). The cross‐linked reverse micelles have good stability in blood environment and resist extreme dilution.…”
Section: Resultssupporting
confidence: 81%
“…Amphiphilic molecule 1 was dissolved in a 2:1 v/v trichloromethane/ N , N ‐dimethylacetamide (DMAc) mixture with a W 0 (water‐to‐surfactant molar ratio) of 5 to form the optically clear reverse micelle solution. [ 15 ] The AICRM was obtained by covalently capturing the reverse micelles in the presence of cross‐linker 2 (see the “Experimental Section” for details). Successful capture was verified by 1 H NMR spectroscopy, which showed that the double bond peaks disappeared from 5.5 to 6.0, and all other peaks broadened (Figure S1, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…RMs with confined water pools have been applied in many fields. Recently it was achieved transfer of RMs from the organic phase to water phase without disturbing their confined water pools and hydrophobic alkyl region providing a suitable environment for newfangled applications such as enzyme‐mimicking catalysis and image‐guided cancer therapy . Regarding the use of RMs as nanoreactors, reactants are solubilized in the water pools in separate micellar solutions to react after mixing, reactions take place as the micelles exchange process inside the droplets (nucleation and growth).…”
Section: Introductionmentioning
confidence: 99%